Program Pendampingan Bakat Kewirausahaan Dan Keterampilan Bisnis Pada Siswa SMA N 9 Kota Bengkulu - Oktaviani, Dytha; Susanti, Neri; Sudarsono, Aji; Subhi, Ramadan; Harwini, Dewi (Jurnal Gotong Royong, 2024)
The implementation of community service activities at SMA Negeri 9 Bengkulu City has provided quality and inspiration to students in entrepreneurship to create a generation of successful young entrepreneurs. The purpose of this activity is to develop business talent into entrepreneurs who think of the latest ideas and trends. The method used in this service is the Participatory Action Research (PAR) approach, which is a research method carried out in a participatory manner among citizens and communities. then the author equips students with entrepreneurial knowledge through the delivery of material, discussions and questions and answers. this activity was carried out for 1 day on July 3, 2024.